Social assistance in Central and Eastern Europe: Features and characteristics - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper reviews the features of social assistance programs in Central and Eastern Europe in the mid 2000s along five dimensions, i.e. expenditure, entitlement rules, benefit levels, centralization of administration, and the provision of additional services. It finds that generally expenditure and benefit levels are low while there is some cross-national variation in the design of eligibility rules, administration and delivery and linkage to additional services. Countries having larger benefits also have more permissive entitlement rules, make available additional services such as health-care or housing, and spend larger fractions of their GDP on this type of programs.
Keywords: D31; H53; I38; I32; 330; social assistance; Central and Eastern Europe; welfare state; program design